2021
DOI: 10.2174/1573399816666201103142102
|View full text |Cite
|
Sign up to set email alerts
|

Glucolipotoxicity-induced Oxidative Stress is Related to Mitochondrial Dysfunction and Apoptosis of Pancreatic β-cell

Abstract: : Glucolipotoxicity-induced oxidative stress and mitochondrial dysfunction of pancreatic β-cells are one of the mechanisms that have been related to the low insulin secretion and cell death during diabetes development. In early or non-chronic stages, the pancreatic β-cells respond to hyperglycemia or hyperlipidemia, stimulating insulin secretion. However, the chronic effect of both leads to the establishment of glucolipotoxicity which induces constant overstimulation of pancreatic β-cells, a condition that lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
0
14
0
2
Order By: Relevance
“…Our data support this framework because GLT decreased the GSH concentration and redox potential; however, TMAO showed no effect on this oxidative mechanism ( Figure 4 A,C).The beneficial TMAO phenotype we observed on β-cell function corresponds with increased IRE1α and decreased P-PERK protein levels during GLT-induced ER stress. β-cell function begins with insulin production via translation and folding at the ER, followed by maturation into secretory granules [ 41 , 45 , 46 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ]. Therefore, ER stress and accumulation of unfolded proteins at the ER plays a major role in T2D β-cell damage [ 115 , 132 , 133 , 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data support this framework because GLT decreased the GSH concentration and redox potential; however, TMAO showed no effect on this oxidative mechanism ( Figure 4 A,C).The beneficial TMAO phenotype we observed on β-cell function corresponds with increased IRE1α and decreased P-PERK protein levels during GLT-induced ER stress. β-cell function begins with insulin production via translation and folding at the ER, followed by maturation into secretory granules [ 41 , 45 , 46 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ]. Therefore, ER stress and accumulation of unfolded proteins at the ER plays a major role in T2D β-cell damage [ 115 , 132 , 133 , 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, the mechanisms of lipotoxicity in pancreatic beta-cells have been extensively studiedmainly in rodent insulin-secreting beta-cell lines and islets due to a scarce supply of human islets. Numerous groups have demonstrated that toxic effects of FFAs in beta-cells involve an induction of oxidative stress, activation of ER stress and mitochondrial dysfunction [ 3 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. The generation of the human EndoC-βH1 beta-cell line [ 57 ] has enabled studies on the specific effects of various FFAs in human beta-cells [ 13 , 14 , 56 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma free fatty acid (FFA) levels have been detected at the prediabetes state and in T2DM patients, and it is believed that chronic exposure of pancreatic insulin-secreting beta-cells to FFAs induce beta-cell dysfunction and death [ 3 , 4 , 5 , 6 ]. FFAs induce a multimodal stress response, including oxidative stress, endoplasmic reticulum (ER) stress and mitochondrial dysfunction, leading to dysfunction and death of beta-cells [ 3 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. The two most abundant dietary FFAs in plasma are saturated palmitic acid (PA) and monounsaturated oleic acid (OA)—of which, OA exerts toxic effects in human pancreatic beta-cells [ 13 , 14 ], in contrast to rodent beta-cells in which it protects from PA-mediated cell death [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Гиперсекреция гормона роста приводит к усилению процессов глюконеогенеза и липолиза, сопровождающихся снижением проницаемости клеточных мембран для глюкозы, усилением секреции инсулина с постепенным истощением инсулярного аппарата. При этом имеют место симптомы гиперфункции гипофиза (акромегалия, гигантизм), сухость слизистых оболочек и кожи, жажда, полиурия [13] [14]. Инсулинорезистентность (ИР), развивающаяся в результате вышеуказанных факторов и являющаяся ведущим патогенетическим механизмом нарушений углеводного обмена при ХОБЛ, и неадекватная секреция инсулина могут усиливать друг друга.…”
Section: роль контринсулярных гормонов в регуляции гомеостаза глюкозыunclassified